Function and Form of Presentation of the Barongan Dance at the Jaranan Pegon Temple in the Clean Ritual of Sumbergedong Village - Aristantya, Dhea; M.Sn, Bambang Sugito (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
This research examines the function and form of presentation which includes the structure and elements of the Barongan Dance. The uniqueness of this research lies in the object studied, namely the barongan dance in the village clean ritual, which is different from the barongan in general which is used as an art performance. The aim of this research is to find out and describe the function and form of the Barongan Dance in the Jaranan Pegon art in the clean ritual of Sumbergedong Village, Trenggalek District. This research uses a qualitative method with a descriptive type. The data collection techniques used are interviews, observation and documentation as well as using data analysis techniques in the form of field data. The research results stated that the function of the barongan dance in filling the clean ritual in Sumbergedong Village, Trenggalek Regency is as a means of ritual, entertainment and aesthetic presentation. The form of Barongan Dance presentation consists of movement, accompaniment or music, clothing, props and performance venue. The structure of the presentation of the Barongan Dance places this dance in the middle or final part of the Jaranan Pegon art performance, starting from the barongan entering the war stage with the jaranan dancers, followed by a trance scene from the selected person, then in the final round, the barongan jamasan procession occurs. The variety of barong dance movements is characterized by repetitive movements. Barongan dancers when experiencing trance display different levels of movement and floor patterns, the floor patterns they create tend to be unstructured and directionless. The type of accompaniment used is external music. Keywords:Barongan, Form, Function